2005
DOI: 10.1097/01.mlg.0000175539.25182.2a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Neck Length on the Safety of Percutaneous and Surgical Tracheotomy: a Prospective, Randomized Study

Abstract: We failed to demonstrate a correlation between CSD and tracheotomy related complications. Patients with short necks may be at no higher risk during either a PDT or ST. Experience, awareness of complications, and a dedicated team approach are necessary for the safe performance of PDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 17 publications
0
34
0
2
Order By: Relevance
“…Previous studies also found no significant differences in the procedure related complications in trainee-led PDT group (Table 6). [10,14,15,[19][20][21][22][23] Bleeding occurred in 5% to 24% of patients who underwent PDT. [7,9,16,24] This study also found a similar incidence rate of bleeding between the trainee and intensivist groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also found no significant differences in the procedure related complications in trainee-led PDT group (Table 6). [10,14,15,[19][20][21][22][23] Bleeding occurred in 5% to 24% of patients who underwent PDT. [7,9,16,24] This study also found a similar incidence rate of bleeding between the trainee and intensivist groups.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure time was 22 minutes(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) in the trainee group and 23 minutes(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) in the intensivist group, showing no significant difference (p = 0.323) (Table 3). PDT-related complications occurred in 23 patients (17%) in the trainee group and 9 (14%) in the intensivist group (p = 0.309).…”
mentioning
confidence: 83%
“…In 1985, Ciaglia et al (43) described percutaneous dilational tracheostomy (PDT) in which tracheostomy is accomplished via modified Seldinger technique, typically with the aid of bronchoscopy (43). A number of clinical studies and secondary data analyses have compared tracheostomy placed by these two approaches and suggest several advantages of PDT relative to surgically created tracheostomy (44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). PDT may be performed at the bedside, thus avoiding the inconvenience and risk associated with transporting a critically ill patient to the operating suite, as well as the expense of using these resources (10,44,49,64).…”
Section: Technique Of Tracheostomy Placementmentioning
confidence: 99%
“…Performing PDT in morbidly obese patients carries an increased, although acceptable, risk for perioperative complications [8,20]. Patients with short necks might be at no higher risk during either a PDT or ST [21]. The decision whether to perform PDT or ST should depend upon the experience of the practitioner and the possibility to identify anatomical landmarks.…”
Section: Discussionmentioning
confidence: 99%